Granulicatella elegans Causing Periorbital Infection During Orthodontic Treatment. Issue 4 (July 2016) - Kim, Yong Joon; Choi, Bo Mi; Choi, Kyung Seek
Abstract : Granulicatella elegans is a normal component of the oral flora and is an unusual causative agent of infective endocarditis. A case of G. elegans periorbital infection of the eyelid after dental treatment is reported. A healthy 35-year-old man presented with painful swelling of the left upper eyelid. He was empirically treated with oral amoxicillin for 1 week. He presented 3 months later with the same clinical features. G. elegans and Staphylococcus epidermidis were identified in bacterial cultures from wound aspirates. Probable relapse of periorbital infection was successfully treated with a 6-week course of oral amoxicillin. This is the first reported case of a non-bloodstream infection caused by G. elegans . Clinicians should be aware of G. elegans as an unusual causative agent of periorbital infection. Within the limitations of this case report, prolonged antibiotic therapy is recommended for a G. elegans periorbital infection to minimize the risk of relapse. Abstract : Clinicians should be aware of Granulicatellaelegans as an unusual causative agent of periorbital infection, and prolonged duration of antibiotic therapy may be helpful to minimize the risk of relapse.